Hubungan Antara Tingkat Pengetahuan dengan Perilaku Hidup Bersih dan Sehat Siswa di Madrasah Ibtidaiyah Muhammadiyah Gonilan Kartasura Sukoharjo - Dirgahayu, Nadia Primivita, dr. Mohammad Shoim Dasuki, M. Kes, dr. Anika Candrasari, M.Kes (2015)
Background: Schools in addition to functioning as a place of learning is also the threat of disease transmission . Diseases that often appear in school-age children ( ages 6-10 ) such as diarrhea , intestinal worms , anemia , dental caries was associated with PHBS. The health problems that occur in children of school age increasingly clear that the values of PHBS in school is still minimal and has not reached the expected level . Many factors influence the implementation of PHBS in schools , one of which is the lack of knowledge about the PHBS. Objective: To know the relationship between the level of knowledge and behavior of living clean and healthy at students of Madrasah Ibtidaiyah Muhammadiyah Gonilan Kartasura Sukoharjo. Methods: Observational analytic studies of non-experimental cross sectional was used in this research. The study was conducted in November 2014 held at Madrasah Ibtidaiyah Muhammadiyah Gonilan Kartasura Sukoharjo with sample students of class 4 , 5 , and 6 as many as 119 students were selected with saturated sampling technique . Hypothesis test used is the Chi-square test with SPSS 17.0 for Windows. Results : p = 0.001 for the level of knowledge and behavior of living clean and healthy, there is a relationship between the level of knowledge with behavior of a clean and healthy living. Conclusion : There is a significant relationship between the level of knowledge and a clean and healthy living behaviors of students at Madrasah Ibtidaiyah Muhammadiyah Gonilan Kartasura Sukoharjo